ANALISIS MANAJEMEN KONFLIK KEPALA MADRASAH DALAM PENDIDIKAN ISLAM: PENYELESAIAN KONFLIK ANTARA GURU, SISWA, DAN ORANG TUA DI MI KOTA PEKANBARU - Akhyar, Yundri (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study analyzes the conflict management strategies implemented by madrasah principals in resolving disputes among teachers, students, and parents at Madrasah Ibtidaiyah (MI) in Pekanbaru City. The study is necessary due to the increasing frequency of conflicts in educational institutions, which can disrupt the learning process and school harmony if not properly managed. Using a descriptive quantitative approach, data were collected through questionnaires distributed to 38 Madrasah Ibtidaiyah principals in Pekanbaru. The collected data were analyzed using descriptive statistics to identify the most commonly used conflict resolution strategies.The findings indicate that principals predominantly use collaboration and compromise strategies, while avoidance is rarely applied. The main causes of conflict are ineffective communication and differences in perception. Most respondents reported improved relationships after conflict resolution, with high satisfaction levels regarding the principals' decisions. Conflict management policies are also sustainable, reflecting consistent efforts. Further research is recommended to assess the long-term impact of conflict resolution strategies on school performance and student learning outcomes.